Voices in the History of Madness
XXII, 430 p. 20 illus., 16 illus. in color.
Keywords: This book presents new perspectives on the multiplicity of voices in the histories of mental ill-health. In the thirty years since Roy Porter called on historians to lower their gaze so that they might better understand patient-doctor roles in the past, historians have sought to place the voices of previously silent, marginalised and disenfranchised individuals at the heart of their analyses. Today, the development of service-user groups and patient consultations have become an important feature of the debates and planning related to current approaches to prevention, care and treatment. This edited collection of interdisciplinary chapters offers new and innovative perspectives on mental health and illness in the past and covers a breadth of opinions, views, and interpretations from patients, practitioners, policy makers, family members and wider communities. Its chronology runs from the early modern period to the 21st century and includes international and transnational analyses from Europe, North America, Asia and Africa, drawing on a range of sources and methodologies including oral histories, material culture, and the built environment. Chapter 4 is available open access under a Creative Commons Attribution 4.0 International License via link.springer.com.